Not About Facts but Emotions? Political Polarisation as a Problem of Redescription - Schledorn, Jeremias (Javnost-The Public, 2024)
Political polarisation, e.g. following the refugee movements of 2015 or the Covid pandemic, is often explained by emotions. The latter are widely exploited as a political strategy, while points of view are often discredited as based on mere emotion rather than “rational” thought. This development challenges the idea of participants being moved by the “unforced force of the better argument” (Habermas 2001) or the idea that consent was the goal of debating. Not only has this resulted in an environment of “post-truth” (Hyvönen 2018), but the motivation of participants to take issue with political questions can be described more interestingly than as a search for truth or a better reasoning.